Sporamin induces apoptosis and inhibits NF-κB activation in human pancreatic cancer cells - Cuijuan Qian; Xiaoying Chen; Yongxiao Qi; Sheng Zhong; Xinyan Gao; Wenjun Zheng; Zhixiang Mao; Jun Yao (Tumor Biology)
Sporamin, a Kunitz-type trypsin inhibitor (TI) from sweet potato tuberous roots, has demonstrated anti-tumor activity through poorly defined mechanisms. Furthermore, the effects of sporamin on pancreatic cancer have not been explored. Herein, we studied the effects of sporamin on two human pancreatic cancer cell lines, PANC-1 and BxPC-3. Sporamin significantly inhibited the cell viability and proliferation activity and induced apoptosis in PANC-1 and BxPC-3 cells. Consistently, in sporamin-treated PANC-1 and BxPC-3 cells, the anti-apoptotic proteins Bcl-2 and Bcl-XL were downregulated and the pro-apoptotic protein Bax was upregulated. Moreover, nuclear factor kappa B activation and IκBα phosphorylation were inhibited, and total IκBα expression was increased in sporamin-treated PANC-1 and BxPC-3 cells. Thus, our results suggest that the anti-tumor effects of sporamin in pancreatic cancer cells might result partly from induction of apoptosis by downregulating nuclear factor kappa B pathway.